Assessment of Bus Stop Infrastructure on Trans Metro Pekanbaru Corridor 1 and Corridor 3 Based on National Transit Standards - Saputra, Heri; Puspita Sari, Neri; Setiani, Yulia; Rini, Silfia (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2025)
Trans Metro Pekanbaru (TMP) is the main public transportation system in Pekanbaru, Indonesia. A critical component supporting the quality of TMP services is the condition and adequacy of its bus stops. This study examines the adequacy of bus stop infrastructure in Corridor 1 (Pandau–Pelita Pantai) and Corridor 3 (UIN Suska–Akses Sudirman Awal Bros) based on national public transportation service standards. This study uses primary data through field observations and secondary data from the Pekanbaru Transportation Agency. The main elements evaluated include physical facilities, service information, spatial planning, and compliance with regulatory standards. The results show that both corridors are lacking in providing adequate passenger facilities and information, with most bus stops categorized as poor. Corridor 1 performs better, especially in terms of bus stop layout and infrastructure quality, due to its alignment through the city center where new facilities have been built. This study highlights the urgent need for improved standards across all TMP corridors to improve public transportation usability and passenger satisfaction.